A comparative study on LiFePO4/C by in-situ coating with different carbon sources for high-performance lithium batteries. (20th January 2018) - Meng, Yanshuang; Xia, Jun; Wang, Lei; Wang, Gongrui; Zhu, Fuliang; Zhang, Yue
Abstract: LiFePO4 /C materials are synthesized via in-situ coating of LiFePO4 by using 1-butyl-3-methylimidazolium dicyanamide ([BMIm][N(CN)2 ]) and glucose as carbon sources, respectively. The structure characterization results indicate that the carbon sources have no effect on the LiFePO4 particles, but have remarkable influence on the coated carbon films. It is found that the [BMIm][N(CN)2 ] carbon source leads to ultrathin (1–2 nm), uniform and highly graphitized carbon films. Due to this unique structure, the electrode materials fabricated by using [BMIm][N(CN)2 ] exhibit a superior electrode reaction reversibility, a capacity retention of 160.6 mAhg −1 (1.47% decay rate) after 50 cycles and a specific discharge capacity of 143.6 mAhg −1 at 1C, which is much better than the performance of the electrode materials synthesized with glucose. Graphical abstract: Graphic abstract: Schematic illustration of the LFP/IAC and LFP/GAC samples. In-situ hydrothermal method is used to synthesize carbon film coated LiFePO4 particles with different carbon sources (IL and glucose). It is found that the IL carbon source can produce ultra-thin carbon film of 1–2 nm, which can not only transport the Li + with a high speed during charge-discharge process but also creates electron paths, thus improving the electrochemical performances. Image 1